DIAGNOSIS OF UNIVERSITY SPORT IN MATO GROSSO DO SUL (MS), BRAZIL (Fiep Bulletin - online, 2013)
Brazil is a country known for its great sporting potential, but also features the often amateur structure of its sport. Not infrequently witness the interviews of athletes speaking about the lack of incentives and structure they face in their daily lives as well as many other difficulties involving Brazilian sportsmen. When we turn our attentions to college sport, that reality sometimes aggravates and the abandonment worsens. Often, athletes use personal financial resources to participate in competitions. They have to pay for their travel, accommodation, food and the value of registration for the event itself. These athletes reconcile studies, jobs and training (in some cases at inappropriate times such as lunchtime or early morning). Turning our gaze to first world countries like the U.S., we can observe a very different reality. The American college sports can be often compared, with professional sports in Brazil. There are many examples, from basketball, football, baseball, golf to NASCAR. Thus, focusing on Brazil, particularly in the Mato Grosso do Sul region, in this study we aim to analyze the current situation of college sports in Mato Grosso do Sul and thereafter propose actions that will promote its development.
Keywords: Sport University; Sports Organization; Sports Management.